2016
DOI: 10.1097/iae.0000000000001076
|View full text |Cite
|
Sign up to set email alerts
|

Features of Optical Coherence Tomography for the Diagnosis of Vogt–koyanagi–harada Disease

Abstract: OCT-related morphological signs have a relatively high predictive value for the diagnosis of acute VKH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 35 publications
1
29
1
2
Order By: Relevance
“…On the other hand, in VKH, these areas could represent inflammatory debris or macrophages engulfing shed outer segments. In fact, Xi et al reported that these areas were seen at a high frequency during evaluations 7 . In our current case, although the angiography showed the presence of choroidal hypoperfusion, there were no RPE defects found on OCT evaluations or any findings of inflammation during the slit lamp examination, such as the presence of both anterior chamber and anterior vitreous cells, flares, or vitreous opacifications.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…On the other hand, in VKH, these areas could represent inflammatory debris or macrophages engulfing shed outer segments. In fact, Xi et al reported that these areas were seen at a high frequency during evaluations 7 . In our current case, although the angiography showed the presence of choroidal hypoperfusion, there were no RPE defects found on OCT evaluations or any findings of inflammation during the slit lamp examination, such as the presence of both anterior chamber and anterior vitreous cells, flares, or vitreous opacifications.…”
Section: Discussioncontrasting
confidence: 44%
“…SRFM has been observed with central serous chorioretinopathy (CSC) and posterior uveitis, such as in Vogt–Koyanagi–Harada disease (VKH) 7 . In CSC, it is possible that intense choroidal hyperpermeability and breaches in the RPE could allow a large molecule, such as fibrin, to enter from the sub-RPE into the subretinal spaces 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The “T” sign (present in 41.2% of reported cases[ 8 ]) indicates fluid accumulation at the sub-Tenon’s space accompanied by enhancive scleral thickness. Recently, investigations of collective OCT findings revealed that the frequency of subretinal mass was exceedingly more common in acute VKH disease patients (80%) than in patients with posterior scleritis (15%); however, the incidence of RPE folds was higher in posterior scleritis patients (62%) than in acute VKH disease patients (55%)[ 8 ]. Our patient showed no signs of iritis in either eye and no signs of predominately neurological and auditory manifestations either.…”
Section: Discussionmentioning
confidence: 99%
“…OCT has been shown to be a useful tool to measure and monitor serous retinal detachments during the acute and chronic stages of VKH disease, with the ability to show shallow serous detachments not otherwise seen [60]. However, OCT is mainly better at showing extrachoroidal spillover retinal involvement and does not give information on subclinical smouldering choroidal disease.…”
Section: Optical Coherence Tomography (Oct) and Enhanced Depth Imaginmentioning
confidence: 99%